Pemanfaatan Media Visual dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Iswan E. Tawari (Peneliti.net, 2022)
Visual media are props used by teachers in the teaching and learning process so that students can enjoy them through sight or the five senses of the eye. This research is a descriptive qualitative research. The research was conducted at Ternate Muhammadiyah High School. The subjects of this study were one student teacher of Pancasila and Citizenship Education and three class X students. The data collection techniques used were observation, interviews, and documentation. This research resulted in (1) the enthusiasm of students in learning subjects that still require attention, cannot be separated from the constraints of both class conditions and study time. Therefore the teacher must be able to control the class so that the class situation is under control again and students can study with concentration, the teacher must be able to read the class situation well. (2) Visual media can make it easier for teachers to provide natural learning material, visual media displays a concrete picture of a material, visual media can also focus student motivation in learning and students easily understand subject matter, and stimulate student activity in learning Pancasila and Citizenship Education. (3) Visual media can provide a real picture of a material because it not only displays text, but also contains images, motion, animation that are interesting to students so that visual media can increase students' teaching and learning desires